Work-Family Conflict and Psychological Stress Among Nurses in Irbid Hospitals - حنان صبحي عبد الكريم بلبيسي; حسني محمّد عوض (Deanship of Scientific Research (DSR), the University of Jordan, 2023)
Objectives: The study aims to identify the attitudes of educational counselors in the Palestinian public schools towards the use of e-counseling in light of the COVID-19 pandemic and its relationship to the professional self. Methods: The study utilizes a relational descriptive approach. It applies two measures: counselors' attitudes towards using e-counseling and their professional self. The data is collected from a stratified random sample of 453 counselors during the academic year 2020/2021. Results: The results indicate that counselors' attitudes towards using e-counseling were positive, with a mean score of 3.19. There is a statistically significant relationship between counselors' attitudes towards using e-counseling and their level of professional self, as indicated by a Pearson correlation coefficient of 0.126. The relationship was positive. The counselors' attitudes towards using e-counseling have a statistically significant predictive ability on their professional self. The results show no statistically significant differences in counselors' attitudes towards e-counseling based on the following variables: gender, educational qualification, place of residence, and directorate. However, there are statistically significant differences in the variable of counseling experience, favoring those with less than two years of experience and those with 5-10 years of experience. Additionally, there are no statistically significant differences in vocational self among the counselors based on variables such as gender, educational qualification, place of residence, and directorate. Conclusions: The study recommends the provision of training programs for counselors to enhance their efficiency in e-counseling.